Owning the city : property rights in authoritarian regimes - Olive, Marsha McGraw (Understanding Europe (Newcastle upon Tyne, England), 2022)
Privately-held property (land and buildings) and the growth of the propertied middle class presents an anomaly in authoritarian states. This book unravels the puzzle that is the growth of private property in tandem with political support for authoritarian regimes.